Pemanfaatan tepung ampas kopi arabika (Coffea arabica) sebagai substitusi tepung terigu (Triticum compactum) dalam pembuatan bolu klemben: Utilizing arabica coffee dregs flour (Coffea arabica) as a substitution of wheat flour (Triticum compactum) in the making of klemben cake - Santoso, Jennifer; Minantyo, Hari (AGROMIX, 2022)
Introduction: Coffee production in Indonesia has increased. Increase of production followed by the increase of consumption of coffee. Increase in consumption of coffee causes the stock of coffee dregs to increase. Coffee dregs come from the making of coffee beverages and coffee dregs usage are still at their minimum usage or coffee dregs are not used or discarded. The purpose of this study is to reduce waste which is coffee dregs and optimize that waste as a substitute material in making food and beverages. Besides that, to know the best treatment and substitution percentage to coffee dried flour klemben cake in texture, color, taste and scent. Methods: This study uses experimental and research and development methods. In this study, researchers use two types of treatment to coffee dregs which are drying using sun and roast and using 10%, 15% and 20% as the substitution percentage. Every sample will be tested by organoleptic test with 30 untrained panelists and repetition will be done 3 times. Results: Based on organoleptic test, the most preferred sample by panelists is coffee dregs flour klemben cake with roast treatment and 10% substitution percentage. Conclusion: Utilization of arabica coffee dregs flour gives influence to the color, taste, scent and texture of the sample. The higher substitution percentage usage of coffee dregs flour causes panelists to dislike the sample more.